Attitude toward money and openness to experience in the formation of marketplace consumer impulse buying - Andyan Pradipta Utama; Alvita Sari; Rahayu Lestari; Subur Karyatun (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Impulse purchases in the digital marketplace are increasing, but the relationship between attitudes towards money, openness to experience, and hedonic shopping motivation has not been studied in an integrated manner. This study aims to analyze the effect of attitudes towards money and openness to experience on impulse purchases, with hedonic shopping motivation as a mediating variable. This research refers to the Theory of Planned Behavior and the Five Factor Model as a theoretical basis. Using a mixed method sequential explanatory approach, quantitative data was collected from 115 marketplace respondents in Jabodetabek and analyzed using PLS-SEM. The qualitative stage was conducted through interviews with 8 informants. Results show that attitude towards money has a significant effect on hedonic shopping motivation (t = 2.491; p = 0.013) and impulse buying (t = 3.917; p = 0.000), but the mediation effect is not significant (t = 1.108; p = 0.268). In contrast, openness to experience had a significant effect on hedonic shopping motivation (t = 4.291; p = 0.000) and impulse purchase (t = 2.395; p = 0.017), and was significantly mediated by hedonic shopping motivation (t = 2.041; p = 0.042). These findings provide strategic implications for digital marketers in developing campaigns based on consumer psychological characteristics. Limitations of this study include sample size and geographical scope.